Políticas de combate à violência contra as mulheres como resultados de múltiplos fluxos nacionais e internacionais: uma análise dos governos de Dilma Rousseff no Brasil (2011-2016) e Cristina Kirchner na Argentina (2007-2015) - Schiavon, Cristina Stern (2024)
This research analyzes the government responses of Dilma Rousseff (2011-2016) in Brazil and Cristina Kirchner (2007-2015) in Argentina, to the demands to combat violence against women, observing the recommendations of the international agenda. There are three theoretical axes that guide this dissertation: Violence Against Women (VCM), International Institutional Mechanisms (MII) and Public Policies (PP) – which have their concepts defined in this study, as well as being used in the Systematic Literature Review carried out here. As procedural methods implemented here, this research uses the Comparative Method, put into practice from the comparison between the Multiple Flow Models (John Kingdon) elaborated through data extracted from the Rousseff and Kirchner governments, and Content Analysis, which was put into practice through the documentary analysis of institutional mechanisms, treaties, conventions, resolutions, legislation and other documents arising from the international agenda related to the United Nations and the Organization of American States, and the national agenda of the States studied here. As observed results, taking advantage of the opening of a Window of Opportunities, Dilma Rousseff's administration produced 8 Public Policies to combat Violence Against Women and Cristina Kirchner's administration produced 11 Public Policies as government responses to the problem of VAW - 3 of which were aimed at the civilian population and 8 for the Argentine military. Such Policies result from the confluence of the three streams presented in the Multiple Streams Model (John Kingdon) – Problem, Politics and Policy.